Can Sub-Saharan Africa Leap Into Global Network Trade ? - Subramanian, Uma (The World Bank, 2007)
This paper examines opportunities for Sub-Saharan African countries to effectively participate in globalization, particularly given the increasing interest of China and India in Sub-Saharan Africa. How can Sub-Saharan Africa fully engage and gain benefits from global network trade? Over the past 15 years Asia has become Africa's fastest growing export market. Asian countries are much more open to trade than Europe or America. There seems to be no evidence to suggest that this trend will not continue in the near future. The authors acknowledge the numerous caveats in Asia's growing interest in the African continent, not least the "resource curse" of exports that are heavily concentrated on oil, minerals, and raw materials, as well as the fierce competition from Asia's cheap manufactured exports. However, they believe that there is strong evidence to suggest a clear potential for South-South cooperation in trade and investment. Drawing on evidence from their extensive research into international value chains, the authors identify five critical factors for effective participation in global network trade: price, speed-to-market, labor productivity, flexibility, and product quality. Underlying competitive performance of these critical factors are a country's policies and institutions. Effective policies, efficient institutions, and the necessary infrastructure will ensure the best outcome for trading countries. To improve the depth and sustainability of these five critical factors, it is important that developing countries create a supportive policy and institutional framework from the outset